The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00464-013-3083-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laparoscopic sleeve gastrectomy on the antireflux mechanism: can it be minimized?

Abstract: LSG weakens the contraction amplitude of the lower esophagus, which may contribute to postoperative reflux deterioration. It also increases the total and the abdominal length of the LES, especially when the angle of His is mostly approximated. However, if this approximation leads to esophageal tissue excision, reflux is again aggravated. Thus, stapling too close to the angle of His should be done cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 33 publications
1
44
2
7
Order By: Relevance
“…Most studies defined GERD based on proton pump inhibitors (PPIs) use, symptoms evaluation, and presence of esophagitis. Only few studies objectively analyzed patients by esophageal manometry and 24-pH monitoring[15,20,29,33,34,38,40,43,44]. …”
Section: Gerd and Lsg: The Evidencementioning
confidence: 99%
“…Most studies defined GERD based on proton pump inhibitors (PPIs) use, symptoms evaluation, and presence of esophagitis. Only few studies objectively analyzed patients by esophageal manometry and 24-pH monitoring[15,20,29,33,34,38,40,43,44]. …”
Section: Gerd and Lsg: The Evidencementioning
confidence: 99%
“…According to some authors, even a small amount of gastric fundus may have a protective role against GERD, as its complete resection could damage the sling fibers at His angle [28], causing a hypotonic LES. On the contrary, Toro et al [29] demonstrated a major recurrence of GERD symptoms in patients with upper pouch.…”
Section: Discussionmentioning
confidence: 99%
“…In others, however, there is no dilation of the proximal gastric pouch where the weakening of the lower esophageal sphincter or the TLESR is the only reason for the development of their de novo reflux [5], [10], [11]. The presence or development of a hiatal hernia may be a contributing factor as well.…”
Section: Discussionmentioning
confidence: 99%
“…Management of this problem is usually medical with proton pump inhibitors (PPI). After medical management, conversion to RYGB is usually recommended for severe reflux that is uncontrolled medically [5]. With our experience in placing the LINX ® system for managing reflux in non-obese patients, we decided to offer this procedure to one of the patients who had been suffering from severe uncontrolled reflux after sleeve gastrectomy.…”
Section: Introductionmentioning
confidence: 99%